Bakkebyråkratiets yttergrense. Hjemmetjenestens møte med eldre med psykiske helseproblemer - Skatvedt, Astrid; Andvig, Ellen; Baklien, Bergljot (Nordisk tidsskrift for helseforskning, 2015)
Street level bureaucracy’s outer limit. Home care service’s meeting with elderly people with mental health problems. This article illuminates framework for home care services’ work with older people with mental health problems living at home. We also focus upon which consequences the framework have upon home care service’s work and care for this group of elderly. The article is based on qualitative data from a municipality in Norway. Our findings point to the professionals’ experiences of limitations to provide holistic care and their various strategies for dealing with these. The professionals described a strong sense of commitment and shortcomings facing elderly with mental health problems. We call attention to a problem of responsivity, with consequences for both professionals and service users. By presenting professionals in home care service as "extreme street level bureaucrats", we expand Lipsky’s theory of street level bureaucrats. Home care service’s encounters with the this group of elderly is seen as the outer limit of street level bureaucracy, based on the major ethical dilemmas professionals experience in their daily work in connection with that they “shall not attend to” elderly’s mental health problems.